The Association Between Early Drinking and Dependence Varies by Drinking Context - Conde, Karina; Peltzer, Raquel I.; Gimenez, Paula V.; Cremonte, Mariana (Frontiers in Behavioral Neuroscience, 2020)
Evidence regarding the association between early drinking (ED) and later dependence is controversial. It has been alternately hypothesized that ED either plays a causal role in the development of dependence or that it is an early marker of increased psychosocial vulnerabilities. Despite a clear rationale for delaying youth consumption, it is important to discern this relationship. However, most epidemiological evidence comes from individual studies and high-income countries. If there is a causal link between ED and dependence, an association at the aggregate level would be expected. Furthermore, if the link is due to biological mechanisms, the association should be rather invariable regardless the drinking context; while if the association is due to psychosocial factors, a wider variability is to be expected. We explored whether the association between ED and dependence varied across countries clustered by their shared contextual drinking characteristics. We used data from 169 countries from the Global Information System on Alcohol and Health of the World Health Organization: ED, alcohol dependence, heavy episodic drinking (HED), actual drinkers and alcohol policy. To cluster countries by their shared drinking characteristics (prevalences of HED and actual drinkers, and alcohol policy) we used, sequentially, two multivariate data reduction techniques: a multiple correspondence analysis and a hierarchic classification; to estimate the association between ED and alcohol dependence, beta regressions were performed, and then adjusted by country income-level and repeated by gender. Results indicated four country clusters: primarily abstainers (class 1), low drinking countries (class 2), high drinking countries (class 3) and very high drinking countries (class 4). Positive relationships between ED and alcohol dependence were found for all the countries in the world and for those in Class 1, and Class 2. No significant relationships were found for Class 3 nor Class 4. These results were similar for males, but not for females. The association between ED and dependence varies according to the drinking context. Our findings either suggest that the ED-dependence association may be due to individual or environmental vulnerabilities that promote consumption, or that if there is a causal link between ED and dependence, it is strongly moderated by psychosocial characteristics.